PENGARUH KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KINERJA KARYAWAN PADA ORGANISASI PUBLIK - Hasan Husaini (PT Saha Kreasi Indonesia, 2026)
Transformational leadership is a leadership style that positively influences employee performance through motivation, inspiration, and individual development. This study aims to analyze the effect of transformational leadership on employee performance in public organizations. The research method used is a qualitative approach through a literature review of relevant scientific sources. The findings indicate that transformational leadership significantly affects productivity, work discipline, motivation, and the quality of public services. Transformational leaders are able to create a conducive work environment, increase employee loyalty, and encourage innovation within organizations. However, the implementation of this leadership style still faces several challenges such as rigid bureaucratic culture, resistance to change, and limited leadership competencies. Therefore, strengthening transformational leadership capacity is essential to sustainably improve the effectiveness of public organizations.